2017
DOI: 10.1002/bse.1949
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Choice of Environmental Sustainability Strategies in Creating a Competitive Advantage

Abstract: Environmental sustainability has often been claimed as a means to providing a competitive advantage by encouraging efficiencies, attracting customers and obtaining business. This work critically considers this idea in the context of the hotel industry by comparing the strategic intent and implementation of sustainability initiatives in hotels across North America. Environmental sustainability strategies can employ a low cost, a differentiated or a hybrid (a combination of the two) approach to creating a compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 60 publications
6
86
0
5
Order By: Relevance
“…In the same vein, one might also argue that given that in recent times businesses in Malawi have been facing serious power‐cuts and water shortages, most of the owner/managers might have been strongly inclined to adopt sound water management practices and renewable energy sources (solar energy) to simultaneously achieve the cost‐effectiveness of their operations and preservation of the environment. Therefore, a positive perception of environmental sustainability, evident in the previous excerpts, might only be achieved when its integration into national business systems is seen as a way of gaining competitive advantage (see also Böttcher and Müller, ; Walker et al ., ; Sullivan and Gouldson, ; Walsh and Dodds, ) and compliance with strong regulatory pressure (see also Sprengel and Busch, ).…”
Section: Findings and Discussionmentioning
confidence: 97%
“…In the same vein, one might also argue that given that in recent times businesses in Malawi have been facing serious power‐cuts and water shortages, most of the owner/managers might have been strongly inclined to adopt sound water management practices and renewable energy sources (solar energy) to simultaneously achieve the cost‐effectiveness of their operations and preservation of the environment. Therefore, a positive perception of environmental sustainability, evident in the previous excerpts, might only be achieved when its integration into national business systems is seen as a way of gaining competitive advantage (see also Böttcher and Müller, ; Walker et al ., ; Sullivan and Gouldson, ; Walsh and Dodds, ) and compliance with strong regulatory pressure (see also Sprengel and Busch, ).…”
Section: Findings and Discussionmentioning
confidence: 97%
“…On the other hand, because the increasing importance of environmental sustainability among customers, environmental issues have become more important to get competitiveness in tourism destinations (Manaktola & Jauhari, ). Walsh and Dodds () showed that there was a positive relationship between competitive advantage, continued economic success, of the hotels and low cost environmental sustainability strategies that consist of cost efficiencies. Jansson, Nilsson, et al () showed that large companies are more interested in environmentally friendly activities such as resource efficiency, recycling, offering green products and services, and having an environment‐friendly management system than small‐ and medium‐sized companies.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental strategies are manifest as either cost reduction, differentiation strategies, or a hybrid of those (Walsh & Dodds, ). They are usually implemented through new products and/or new services (Jakobson and Clausen ()).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%